Pengaruh Intensitas Persediaan dan Thin Capitalization terhadap Tingkat Agresivitas Pajak Perusahaan - Sudiyatmoko, Agus; Ridwan, Muhamad; Syahputra, Andri (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
This research aims to determine and prove the effect of Inventory Intensity and Thin Capitalization on Tax Aggressiveness in consumer goods sector companies listed in Jakarta Stock Exchange during the period 2019 to 2023. The sample used in this research was 7 companies listed on Jakarta Stock Exchange using purposive sampling technique. The data used in this research is secondary data in the form of financial reports from each company that has been sampled. The variables used in this research are Inventory Intensity (X1), Thin Capitalization (X2), and Tax Aggressiveness (Y). Analysis of the results of this study using the help of E views 12 software by analyzing descriptive statistics, model estimation tests, classical assumption tests, T statistical tests, F statistical tests, and determination coefficient tests.The results showed that partially Inventory Intensity, has no effect on Tax Aggressiveness and Thin Capitalization affects Tax Aggressiveness. As for together (simultaneously) Inventory Intensity and Thin Capitalization affect Tax.